2017
DOI: 10.1177/1087054717702245
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sluggish Cognitive Tempo Symptoms and Attentional Network and Working Memory in Primary Schoolchildren

Abstract: Our results suggest that SCT symptoms are associated with a neuropsychological profile that is different from the classical ADHD profile and characterized by slower reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Taken together, it turns out that SCT is related to deficit in early selective attention regardless of the levels of ADHD symptoms (Lovett et al, 2020;Wood et al, 2020). Thus, SCT would be understood as a slow cognitive process, especially early selective attention, which develops through independent or interactive causes and developmental pathways, for example, other cognitive systems, the negative balance system, and arousal/regulatory systems in a Research Domain Criteria (RDoC) framework (Becker and Willcutt, 2019). Further research would boost the understanding of the nature of SCT that views it from various perspectives and links it to other related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, it turns out that SCT is related to deficit in early selective attention regardless of the levels of ADHD symptoms (Lovett et al, 2020;Wood et al, 2020). Thus, SCT would be understood as a slow cognitive process, especially early selective attention, which develops through independent or interactive causes and developmental pathways, for example, other cognitive systems, the negative balance system, and arousal/regulatory systems in a Research Domain Criteria (RDoC) framework (Becker and Willcutt, 2019). Further research would boost the understanding of the nature of SCT that views it from various perspectives and links it to other related factors.…”
Section: Discussionmentioning
confidence: 99%
“…While attentional problems have been repeatedly proven to exist in those with SCT (e.g., selective attention), mixed results were reported regarding the information processing that is affected by attention (Mueller et al, 2014 ; Barkley, 2018 ; Becker and Barkley, 2018 ; Kofler et al, 2019 ). For example, those with SCT showed impaired information processing including visual-perception, attention network, and processing speed (Camprodon-Rosanas et al, 2017 ; Wood et al, 2017 ; Jacobson et al, 2018 ; Tamm et al, 2018 ). However, several studies found no relation between SCT symptoms and processing speed, spatial memory, and response inhibition (Skirbekk et al, 2011 ; Bauermeister et al, 2012 ; Jarrett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…24 More specifically, delayed maturation of brain systems including the frontal cortex is also consistent with core SCT symptoms, such as reduced speed of cognitive processing, apathy and deficient motivation. 8,15,19 In previous studies 18,19 we found that some socioeconomic indicators, dyslexia, inattention symptoms and exposure to smoking at home increase the risk of SCT. We also found that SCT symptoms are associated with a neuropsychological profile that is different from the classical ADHD profile, characterized by slower reaction times.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…SCT-CBCL has previously been extensively used. 5,9,13,18,19,24,25 A study with general population established a cut-off point where all raw scores above the 95th percentile could indicate impairment. 6 Twenty children (11.2%) were above this cut-off in our study.…”
Section: Sluggish Cognitive Tempo (Sct)-child Behavior Checklist (Cbcl) Scalementioning
confidence: 99%
See 1 more Smart Citation